Isolation and characterization of native Bacillus thuringiensis strains from Saudi Arabia with enhanced larvicidal toxicity against the mosquito vector Anopheles gambiae (s.l.). Issue 1 (December 2016) - El-kersh, Talaat; Ahmed, Ashraf; Al-sheikh, Yazeed; Tripet, Frédéric; Ibrahim, Mohamed; Metwalli, Ali
Abstract Background Worldwide, mosquito vectors are transmitting several etiological agents of important human diseases, including malaria, causing millions of deaths every year. In Saudi Arabia, as elsewhere, vector-control is based mostly on chemical insecticides which may be toxic and cause environmental deprivation. Here, to support the development of bio-pesticide alternatives, a study was conducted to identify nativeBacillus thuringiensis (Bt ) isolates with improved toxicity against the malaria vector, Anopheles gambiae (s.l .). Methods Sixty-eightBt isolates were obtained from 300 soil and other samples collected from 16 sites across Saudi Arabia.Bt identification was based on morphological characteristics of colonies, shape of parasporal crystals and biochemical profiles. After characterization of their mosquitocidal activity, larvicidal strains were described through 16S ribosomal DNA gene sequencing, cry, cyt andchi genes PCR-amplification profiles, and SDS-PAGE protein analyses. Results SphericalBt crystals were predominant amongst the 68 isolates (34%), while irregular, bi-pyramidal and spore-attached crystals were found in 32, 13 and 21% of strains, respectively. LC50 and LC90 bioassays showed that 23/68 isolates were larvicidal, with distinct biochemical activity profiles compared to non-larvicidalBt strains. Eight larvicidal strains showed larvicidal activity up to 3.4-fold higher (LC50 range: 3.90–7.40 μg/ml) than the referenceBti- H14 strain (LC50  = 13.33 μg/ml). Of these, 6 strains hadcry andcyt gene profiles similar toBti -H14 (cry4Aa, cry4Ba, cry10, cry11, cyt1Aa, cyt1Ab, cyt2Aa ). The seventh strain (Bt 63) displaying the highest larvicidal activity (LC50  = 3.90 μg/ml) missed thecry 4Aa andcyt 1Ab genes and had SDS-PAGE protein profiles and spore/crystal sizes distinct fromBti- H14. The eight strain (Bt 55) with LC50 of 4.11μg/ml hadcry andcyt gene profiles similar toBti -H14 but gave achi gene PCR product size of 2027bp. No strains harbouringcry2, cry17 + 27, cry24 + 40, cry25, cry29, cry30, orcyt2Ba were detected. Conclusion This study represents the first report of several Saudi indigenousBt strains with significantly higher larvicidal efficacy againstAn. gambiae than the referenceBti -H14 strain. The very high toxicity of theBt 63 strain, combined with distinctcry andcyt genes and SDS-PAGE-protein profiles makes it a promising candidate for future applications in mosquito bio-control.